Reliability and convergent and discriminant validity of the Child Oral Health Impact Profile (COHIP Child’s version) - Broder HL, Wilson-Genderson M (Blackwell Synergy, 2007)
The purpose of the current study was to assess the reliability as well as the convergent and discriminant validity of the Child Oral Health Impact Profile (COHIP)